Early Infantile Hemophagocytic Lymphohistiocytosis Masquerading as Late-onset Sepsis: A Case Report with Review of the Literature - L. Ramitha; Amith Ahmed; Laxmi Kamath; Deepa Mohan Sharma; Prathap Chandra (Wolters Kluwer Medknow Publications, 2024)
Background: Hemophagocytic lymphohistiocytosis (HLH) is a condition due to uncontrolled overactivation of macrophages, cytotoxic T cells, and natural killer cells creating a cytokine storm, characterized by multiorgan involvement. Familial HLH (fHLH) is due to genetic defects and presents early in life. There are only a few reports of neonatal onset of fHLH. Clinical Description: A 40-days-old male baby, born at 36 weeks of gestation, presented with fever, abdominal distension, poor feeding, lethargy, seizures. He had metabolic acidosis, respiratory failure, hepatosplenomegaly and bicytopenia, with a deranged coagulation profile. Management and Outcome: Treatment was started as per sepsis with meningitis with disseminated coagulation profile. All cultures were sterile, bacterial and fungal polymerase chain reaction were negative, but the baby deteriorated rapidly to shock. As the baby fulfilled the HLH criteria, he was started on intravenous immunoglobulin, methylprednisolone, and immunomodulator anakinra while sending sample for whole-exome sequencing for primary HLH. However, the baby succumbed to the illness. Whole-exome sequencing revealed a perforin-1 gene defect which confirmed primary HLH type 2. Conclusion: This report creates awareness that a primary genetic HLH may mimic early infantile sepsis. The rapidly progressive course in an otherwise healthy, breast-fed baby, with no setting of sepsis, and absence of infective etiology, should raise a suspicion of this underlying potentially fatal condition.